Telephone triage for obstetrics & gynecology - Long, Vicki E.; McMullen, Patricia C. (Wolters Kluwer, 2018)
This title is designed for use by professional nurses assessing and advising patients over the telephone on topics related to obstetrics and gynecology. It is designed to crystalize the professionals existing knowledge base and to provide clear guidance on handling a wide-variety of patient situations.